How Information on a Motive to Lie Influences CBCA-Based Ratings and Veracity Judgments - Schemmel, Jonas; Steinhagen, Tina; Ziegler, Matthias; Volbert, Renate (Frontiers in Psychology, 2020)
We investigated how information on a motive to lie impacts on the perceived content quality of a statement and its subsequent veracity rating. In an online study, 300 participants rated a statement about an alleged sexual harassment on a scale based on Criteria-based Content Analysis (CBCA) and judged its veracity. In a 3 x 3 between-subjects design, we varied prior information (motive to lie, no motive to lie, no information on a motive) and presented three different statement versions of varying content quality (high, medium, low). In addition to anticipating main effects of both independent variables (motive information and statement version), we predicted that the impact of motive information on both ratings would be highest for medium quality statements, because their assessment is especially ambiguous (interaction effects). Contrary to our hypotheses, results showed that participants—unaffected by motive information—accurately reproduced the manipulated quality differences between statement versions in their CBCA-based judgments. In line with the expected interaction effect, veracity ratings decreased in the motive-to-lie group compared to controls, but only when the medium- and the low-quality statement were rated (truth ratings dropped from ~ 80% to ~ 50%). Veracity ratings in both the no-motive-to-lie group and controls did not differ across statement versions (≥ 82% truth ratings). In sum, information on a motive to lie thus encouraged participants to consider content quality in their veracity judgments by being critical only of statements of medium and low quality. Otherwise, participants judged statements to be true irrespective of content quality.